Biomimetic nanostructures/cues as drug delivery systems: a review. (September 2019) - Rasheed, T.; Nabeel, F.; Raza, A.; Bilal, M.; Iqbal, H.M.N.
Abstract: With key scientific advances, researchers are now able to understand biological structures shapes, processes, and mechanisms. The exploitation of these biological fundamentals is a growing area of biomedical research to produce highly efficient and eco-friendly solutions to offer better health facilities. In recent years, the use of naturally inspired structures and processes have gained high research interests to develop numerous types of drug delivery systems (DDSs) to tackle various diseases of high concern. Biologically inspired materials along with both internal and external stimuli-responsive behaviors can be used to engineer advanced DDSs, the so-called 'smart DDS.' Biobased constructs with biomedical potentialities either resemble biological structures to produce similar kind of response or synthesize using a biologically inspired process to avoid their possible failure or rejection. Several DDSs have shown great potential for successful treatment of diseases by specific targeting to diseased tissue with enhanced drug efficiency, bioavailability, and biocompatibility. Subject to the application type and purpose, the nanocarrier-based DDSs are considered potential candidates to deliver biopharmaceuticals. Herein, we reviewed the biomimicry of various DDSs at the nanoscale. Emphasis is given to the DDS based on nanoparticles, nanofibers, micelles, liposomes, and hydrogels. The biomimicry of each of the aforementioned DDSs has also been highlighted, with respect to their action mechanisms and use as novel carriers for biomedical applications at large and drug delivery, in particular. Highlights: Herein, the biomimicry of various drug delivery systems (DDSs) at the nanoscale level is reviewed. Biomimetic nanostructures/cues offer great potentialities to engineer smart DDSs. Concerning action mechanisms and use as carriers for biomedical and drug delivery applications are discussed.